Prevalence of Stunting in Syrian Refugee Children With Cleft Lip and/or Cleft Palate in Time of Crisis: A Call for Intervention. (October 2020) - Chaya, Bachar F.; Chalhoub, Rawad; Jaafar, Rola; Nahhas, Nour; Abu-Sittah, Ghassan
Objective: Our study aims to compare the prevalence of stunted growth in Syrian refugee children with cleft lip and/or palate (CL±CP) to other children with CL±CP of similar socioeconomic status. Design: A retrospective medical chart review. Setting: Center for Cleft and Craniofacial Surgery at a tertiary care hospital in Lebanon in the period between January 2013 and May 2019. Patients, Participants: One hundred three Syrian refugee children and 70 Lebanese children <18 years of low socioeconomic status who have CL, CP, or both. Interventions: These patients underwent cleft repair surgeries at our center. Main Outcome Measure(s): Stunted growth measured by calculating the height-for-age z-score (HAZ). Results: Using a confidence interval of 95%, the prevalence of stunting is significantly higher among Syrian refugees ( P < .003). The prevalence of stunting and age of presentation were positively correlated ( P < .02). There was no difference in stunting between patients with CP and CL ( P < .746). There was no difference in stunting between genders. Conclusions: The majority of Syrian refugee patients with CL±CP fall on the malnourished side of the nutritional spectrum as reflected by the high percentage of stunting as well as a mean of −1 for the HAZ.